‘DIALOG HIDUP’: KUNCI MENUMBUHKAN KOHESIVITAS SOSIAL - Farhanah Farhanah; Fauzia Dian Ummami; Nur Kafid (UIN Raden Mas Said Surakarta, 2015)
Diversity is undeniable reality by everyone in this world.Including diversities in the term of religion and believe. Indonesia haswell known country in the world with its plurality. This plurality, inthe one side, has become uniqueness character and wealth comparedto the other countries. While on the other sides, this pluralitysometimes has also become ‘threat’ for the county’s unity. Variousefforts to build and promote social cohesion within diversities havebecome real requirement to be able to realize the peaceful andharmonious life. One of those efforts is promoting value of tolerancethrough dialogue. Not just an ordinary dialogue, but ‘dialogue oflive’. Dialogue based on the real face to face experiences. Theexperience which is further be able to bring understanding about thediversity of life.